The accuracy of objective threshold determination at low frequencies: comparison of different auditory brainstem response (ABR) and auditory steady state response (ASSR) methods - Frank, Jacqueline; Hoth, Sebastian (International journal of audiology, 2017)
Objective: The hearing threshold at 500 Hz was estimated using five methods which are suitable for the low frequency range: Low-Chirp BERA (LCBERA), Notched-noise BERA (NNBERA), Narrow band CE-Chirp BERA (NBCBERA) and Narrow band CE-Chirp ASSR (NBCASSR) (40/90 Hz). The slope of the discrimination function of each method was used for determination of the most efficient method. The threshold values were compared and the corresponding odds ratios (OR) were calculated. Design: All methods were applied to each subject. Stimulus levels were arranged individually. Response detection was carried out by visual inspection of the records in case of BERA and automatically in case of ASSR. Each individual series of recordings was converted to a dichotomous function indicating whether or not a response was discernible and a continuous method-specific discrimination function was constructed. This function was realised by a Boltzmann function whose slope in the inflection point serves as quality measure. Additionally, an OR evaluation was carried out in order to validate the significance of results. Study sample: Twenty five normal hearing adults (aged 18-30 years) were tested. Results: LCBERA proved to have the highest reliability according to the slope of the Boltzmann function, the comparison of threshold values and OR. Conclusions: The LCBERA is recommended for use in routine clinical practice.
Gesehen am 23.04.2018